Recent Progress in Interferon Therapy for Myeloid Malignancies - Healy, Fiona M.; Dahal, Lekh N.; Jones, Jack R.E.; Floisand, Yngvar; Woolley, John F. (Frontiers in Oncology, 2021)
Myeloid malignancies are a heterogeneous group of clonal haematopoietic disorders, caused by abnormalities in haematopoietic stem cells (HSCs) and myeloid progenitor cells that originate in the bone marrow niche. Each of these disorders are unique and present their own challenges with regards to treatment. Acute myeloid leukaemia (AML) is considered the most aggressive myeloid malignancy, only potentially curable with intensive cytotoxic chemotherapy with or without allogeneic haematopoietic stem cell transplantation. In comparison, patients diagnosed with chronic myeloid leukaemia (CML) and treated with tyrosine kinase inhibitors (TKIs) have a high rate of long-term survival. However, drug resistance and relapse are major issues in both these diseases. A growing body of evidence suggests that Interferons (IFNs) may be a useful therapy for myeloid malignancies, particularly in circumstances where patients are resistant to existing front-line therapies and have risk of relapse following haematopoietic stem cell transplant. IFNs are a major class of cytokines which are known to play an integral role in the non-specific immune response. IFN therapy has potential as a combination therapy in AML patients to reduce the impact of minimal residual disease on relapse. Alongside this, IFNs can potentially sensitize leukaemic cells to TKIs in resistant CML patients. There is evidence also that IFNs have a therapeutic role in myeloproliferative neoplasms (MPNs) such as polycythaemia vera (PV) and primary myelofibrosis (PMF), where they can restore polyclonality in patients. Novel formulations have improved the clinical effectiveness of IFNs. Low dose pegylated IFN formulations improve pharmacokinetics and improve patient tolerance to therapies, thereby minimizing the risk of haematological toxicities. Herein, we will discuss recent developments and the current understanding of the molecular and clinical implications of Type I IFNs for the treatment of myeloid malignancies.